2011
DOI: 10.1159/000329884
|View full text |Cite
|
Sign up to set email alerts
|

Early versus Late Pulmonary Rehabilitation in Chronic Obstructive Pulmonary Disease Patients with Acute Exacerbations: A Randomized Trial

Abstract: Background: Around the world, the timing of referral of chronic obstructive pulmonary disease (COPD) patients for pulmonary rehabilitation differs from immediately after exacerbation (early) to later on when patients are in a stable state (late). There are no trials comparing the different time points of referral for pulmonary rehabilitation. Objectives: Our aim was to compare the effects of early and late pulmonary rehabilitation on exacerbation rates and health-related quality of life (HRQOL) in COPD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 34 publications
1
39
0
4
Order By: Relevance
“…Keeping in mind the deleterious effects of exacerbations on limb muscles, several interventions to prevent or counteract muscle impairment have been considered (522). These interventions, mainly based on exercise training, have been used during, immediately after, or late after the exacerbation (523). A Cochrane Collaboration metaanalysis revealed that pulmonary rehabilitation immediately after an exacerbation significantly improved exercise capacity in addition to reducing hospital admissions and mortality (524).…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…Keeping in mind the deleterious effects of exacerbations on limb muscles, several interventions to prevent or counteract muscle impairment have been considered (522). These interventions, mainly based on exercise training, have been used during, immediately after, or late after the exacerbation (523). A Cochrane Collaboration metaanalysis revealed that pulmonary rehabilitation immediately after an exacerbation significantly improved exercise capacity in addition to reducing hospital admissions and mortality (524).…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…To date, only one study has compared ‘early’ post-exacerbation pulmonary rehabilitation with ‘late’ post-exacerbation pulmonary rehabilitation (delivered 6 months after exacerbation) with an 18-month follow-up 118. No significant differences were seen in health-related quality of life or exacerbation rates between the groups.…”
Section: Evidencementioning
confidence: 99%
“…From 12 potential abstracts; nine compared early post-exacerbation pulmonary rehabilitation with usual care; one was a review paper and the ‘early’ intervention in one study was more than 4 weeks after exacerbation. Only one study was reviewed in full 118. This compared ‘early’ (within 2 weeks of exacerbation) with ‘late’ pulmonary rehabilitation delivered 6 months after exacerbation.…”
Section: Evidencementioning
confidence: 99%
“…A delayed offer of rehabilitation may be more feasible given the immediate psychological impact of the disease. The only reported attempt of an early versus delayed rehabilitation intervention did not report a successful outcome [37] and more recently, a North American study reported similar recruitment difficulties for trial comparing pulmonary rehabilitation with a modest physical activity intervention [38].
FIGURE 1An audit of the post-hospitalisation pulmonary rehabilitation pathway in a northwest London hospital.
…”
Section: Post-exacerbation Rehabilitation: the Evidence And The Challmentioning
confidence: 99%